Extent of Improvement in the Production of Gram Among the Beneficiaries of NFSM in Southern Rajasthan - Ramlal Khatik , F. L. Sharma and H. K. Jain, (Indian Journal of Extension Education, 2017)
The present study was conducted at Banswara and Udaipur districts of Southern Rajasthan. Total eighty NFSM grambeneficiary farmers were selected on the basis of random sampling method from the identified districts. From the study itwas found that out of the 80 respondents before initiation of NFSM, 41 respondents were categorized in low level of yieldof gram, whereas 33.75 respondents were placed in medium yield category and only 12 respondents possessed high levelof yield of gram. Whereas after initiation of NFSM project, 50.00 per cent respondents could be placed under mediumlevel of increase in yield group. It was further noted that only 8 (10.00%) gram growers and 32 (40.00 %) respondentspossessed high level of increase in yield of gram crop.